2020
DOI: 10.3389/fmicb.2020.00105
|View full text |Cite
|
Sign up to set email alerts
|

MiR-10a-5p-Mediated Syndecan 1 Suppression Restricts Porcine Hemagglutinating Encephalomyelitis Virus Replication

Abstract: Porcine hemagglutinating encephalomyelitis virus (PHEV) is a single-stranded RNA coronavirus that causes nervous dysfunction in the infected hosts and leads to widespread alterations in the host transcriptome by modulating specific microRNA (miRNA) levels. MiRNAs contribute to RNA virus pathogenesis by promoting antiviral immune response, enhancing viral replication, or altering miRNA-mediated host gene regulation. Thus, exploration of the virus-miRNA interactions occurring in PHEV-infected host may lead to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…While there are no agomir-based drugs currently approved for coronavirus infections, several studies have reported positive results for this drug class in the in vivo protection against influenza A (H1N1) [13] and hepatitis B [33] viral infections. Notably, one study found that an agomir of miR-10a-5p was able to prevent the replication of porcine hemagglutinating encephalomyelitis virus (PHEV) in mice [34]. Although PHEV does not pose a threat to humans, it is part of the coronavirus family [35], suggesting that agomir therapy may have efficacy against other coronaviruses, notably SARS-CoV-2, MERS-CoV, and SARS-CoV.…”
Section: Discussionmentioning
confidence: 99%
“…While there are no agomir-based drugs currently approved for coronavirus infections, several studies have reported positive results for this drug class in the in vivo protection against influenza A (H1N1) [13] and hepatitis B [33] viral infections. Notably, one study found that an agomir of miR-10a-5p was able to prevent the replication of porcine hemagglutinating encephalomyelitis virus (PHEV) in mice [34]. Although PHEV does not pose a threat to humans, it is part of the coronavirus family [35], suggesting that agomir therapy may have efficacy against other coronaviruses, notably SARS-CoV-2, MERS-CoV, and SARS-CoV.…”
Section: Discussionmentioning
confidence: 99%
“…Past investigations on non-coding microRNAs (miRs) have opened up new possibilities particularly into development of malignancies and their therapy, but this remains a vastly understudied area in the case of SARS-CoV. The significant changes in endogenous miR profiles of cells transfected with porcine hemagglutinating encephalomyelitis virus (HEV), for example, have been noted ( Fan et al, 2020 ; Hu et al, 2020 ). miR-1246 was recently linked to regulation of ACE2 expression in airway epithelium ( Zhang et al, 2020b ) and several miRs have been predicted to bind to the SARS-CoV-2 genome ( Chen and Zhong, 2020 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Such miRs could serve as RNAi targets and/or might be deployed directly (either as miR mimics or anti-miRs), or indirectly as a result of modulation with pharmacological agents. Identifying the pertinent miRs and revealing their mechanistic involvement is bound to provide effective leads not predicted before, such as the case of Syndecan 1 involvement, which is regulated by miR-10a-5p, and whose mimic significantly altered the course of HEV replication ( Hu et al, 2020 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…For example, porcine hemagglutinating encephalomyelitis virus (PHEV), a member of the genus Betacoronavirus that causes nervous system disorders in its host, has been reported to constitutively upregulate the expression of miR-10a-5p in host cells. Treatment with an miR-10a-5p mimic leads to enrichment of miR-10a-5p and a substantial decrease in PHEV replication, suggesting extensive negative control of RNA virus infection by miR-10a-5p [ 54 ]. It was also found that miR-21a-5p was significantly upregulated in the brains of mice, leading to negative regulation of Caskin1 (CASK-interactive protein1) through direct binding to the 3′-UTR of this gene.…”
Section: Role Of Mirnas In Cov Infectionmentioning
confidence: 99%